ANALISIS NILAI COMPUTED TOMOGRAPHY DOSE INDEX (CTDI) PHANTOM KEPALA MENGGUNAKAN CT DOSE PROFILER DENGAN VARIASI PITCH - Sari, Devi Artika; Setiawati, Evi; Arifin, Zaenal (BERKALA FISIKA, 2020)
The purpose of this study was to measure the value of computed tomography dose index (CTDI) using the CT dose profiler, to compare the values of CTDI obtained in the five holes within the head of polymethil-methacrylate (PMMA) phantom, and to analyze the effect of pitch on CTDI values. The CTDI values were measured with the pitch variations of 0.562, 0.938, 1.375, and 1.750. The phantom was scanned with fixed parameters of 120 kVp, 200 mAs, 10 mm width collimation, 150 mm scan length, and 0.50 s tube rotation. Measurements were conducted at Kensaras hospital using the CT scannner of GE Optima CT580 16 slice. The results showed that if the pitch increases, the CTDI will decrease (< 25 mGy). The highest CTDI is 55,36 mGy and it is found on a pitch of 0,562 at upper hole of phantom (B position), and the lowest CTDI is 11,9 mGy and it is found a pitch of pitch 1,750 within a hole at three o’clock position (C position). If the pitch < 1, then the high CTDI is obtained (> 50 mGy) and it takes longer to scan.